2017
DOI: 10.3390/ma10111281
|View full text |Cite
|
Sign up to set email alerts
|

Perspective for Fibre-Hybrid Composites in Wind Energy Applications

Abstract: Increasing the efficiency of wind turbines will be vital for the wind energy sector to continue growing. The drive for increased efficiency is pushing turbine manufacturers to shift from glass fibre composite blades towards carbon/glass fibre-hybrid composite blades. This shift brings significant challenges in terms of optimising the design and understanding the failure of these new blade materials. This review therefore surveys the literature on fibre-hybrid composites, with an emphasis on aspects that are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 120 publications
(261 reference statements)
0
20
0
Order By: Relevance
“…On the other hand, glass fibres (GF) which have much lower strength than carbon fibres but are tougher due to higher strain-to-failure. It has been proved that incorporation of GF into CF is possible to improve the failure strain of CFRP, turning the materials to a combination system called hybrids [2] [3]. Apart from the toughness issue, CF are also very expensive which is regarded as the main drawback why CFRP are only popular in aero industries and automotive sector where weight saving is considered to be the primary concern [3].…”
Section: Hybrid Carbon Glass Fibre Reinforced Polymer (C/gfrp)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, glass fibres (GF) which have much lower strength than carbon fibres but are tougher due to higher strain-to-failure. It has been proved that incorporation of GF into CF is possible to improve the failure strain of CFRP, turning the materials to a combination system called hybrids [2] [3]. Apart from the toughness issue, CF are also very expensive which is regarded as the main drawback why CFRP are only popular in aero industries and automotive sector where weight saving is considered to be the primary concern [3].…”
Section: Hybrid Carbon Glass Fibre Reinforced Polymer (C/gfrp)mentioning
confidence: 99%
“…Several scholars provide recommendations for experimental measurements of the hybrid effect, which is a synergetic increase of the failure strain of low elongation fibres when hybridised with higher elongation fibres. The hybridisation may also result in the improvement of composites mechanical properties characterised by the increase of ultimate tensile strain compared with those of low elongation non-hybrid fibre reinforced composites [2][5][6] [5]. Like most materials, fibre reinforced polymers (FRP) face the strength versus toughness dilemma.…”
Section: Tensile and Flexural Behaviour Of Hybrid Composite Materialsmentioning
confidence: 99%
“…The aim of this study was to develop novel unidirectional hybrid fabrics and their composites with different hybrid configurations, namely interply and intraply, and investigate their mechanical performance in tensile and compressive loading vis-à-vis reference homogeneous non-hybrid composites. Moreover, this study specifically focused on application developments for hybrid composites specifically in the field of sports and leisure products such as skies and wind blade applications such as spar caps [20,30,33,34]. Section 2 addresses the materials, reinforcement and composite fabrication methods and the test procedures to characterise the composite properties.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, synthetic fibers such as Carbon fiber, Glass and Aramid fibers are mixed and matched to improve mechanical performance [23][24][25]. Swolfs et al [35] recommended Carbon/Glass composite for multidirectional loading applications such as wind turbine blades. Valenca et al [23] showed that combining Glass and Kevlar highly improved mechanical strength and impact performance, when compared to plain Kevlar.…”
Section: Multifiber Hybrid Compositesmentioning
confidence: 99%